PEMBERDAYAAN MASYARAKAT DALAM BIDANG KESEHATAN MELALUI PEMERIKSAAN KESEHATAN GRATIS DI DESA BATU LAYAR (Jurnal Pengabdian Masyarakat Sehati, 2023)
Degenerative disease is a disease that can cause death in sufferers. This disease can occur in anyone and at any age. Degenerative diseases, if not treated properly, can cause complications and even death in both urban and rural communities who experience poor lifestyles. Several degenerative diseases that can occur include diabetes mellitus, stroke, arthritis and joint pain. This disease can be diagnosed by carrying out laboratory examinations such as examinations using POCT (Point Of Care Test) as screening examination data. Therefore, it is necessary to carry out outreach and laboratory examinations to help the public monitor their health so they can find out the current condition and proceed to further examinations if there are indications that the examination results are abnormal. This activity was carried out by lecturers, students, and health workers from Medica Farma Husada Mataram Polytechnic, Stikes Yarsi Mataram, and Gunung Sari Community Health Center. The number of participants who took part in this activity was 58 people consisting of 25 men and 33 women. There are 3 laboratory tests carried out, namely blood glucose, cholesterol and uric acid. The results of the examination showed that blood glucose was above normal in 15 people, cholesterol in 23 people, and uric acid in 8 people. Because there are participants who get results above normal, they are advised to go to the Community Health Center for further examination. Apart from that, people are becoming more aware of the importance of medical check-ups to prevent disorders of human body organs, especially the elderly.